Analysis of Pepsi Brand Advertising Implementation Using #Betterwithpepsi for Fast Food Brands - Fadly Rosny (Journal of Social Research, 2024)
Pepsi's recent advertisement campaign, which features the tagline #BetterWithPepsi, was launched in honor of National Burger Day. The campaign has been promoted across all social media platforms and showcases portraits of fast-food packaging that incorporate Pepsi's signature colors into the branding of popular fast-food chains such as Burger King, McDonald's, and Wendy's. This advertisement has been analyzed using semiotic theory by Roland Barthes, who suggests that the use of the advertisement is akin to a collaboration or combination between fast food and drinks that complement each other, such as Pepsi. The tagline #BetterWithPepsi implies that the public will consume food and drinks that are always together, thereby creating a mindset that associates the consumption of food with the use of Pepsi. The advertisement's use of semiotics is evident in the incorporation of Pepsi's colors into the branding of other fast-food chains, which creates a visual association between the two. This association is further reinforced by the tagline, which suggests that the consumption of food is incomplete without the addition of Pepsi. The advertisement's effectiveness can be attributed to its ability to tap into the public's desire for convenience and the need for a complete dining experience. By positioning Pepsi as an essential component of the fast-food experience, the advertisement creates a sense of loyalty and brand recognition among consumers.